Screening for diabetes mellitus among the rural population applying Indian diabetes risk score in field practice areas of Kamineni Academy of Medical Sciences and Research Centre - M. N., Rama Krishna; B., Manoj Aravind; Singh C., Sunil Pal; Reddy, P. Narasimha (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally an estimated 422 million adults are living with Diabetes as per WHO data 2014, and 85 to 90% cases are type 2 diabetes. Maximum number of people with diabetes mellitus are in the age group of 40 to 59 yrs. Among them 50% are undiagnosed. Sedentary lifestyle, diet, dietary fiber, mal-nutrition, some chemical agents, stress, alcohol, viral infections, etc., are some environmental risk factors. Methods: A cross sectional, community based study. Details of the study subjects were recorded using structured predesigned and pretested questionnaire. All the data collected was entered and analyzed with MS Excel software 2007 and Epi info 3.5.3. All tests were considered significant at p <0.05 level. Results: In our study, majority of population participated in the screening camp are between 30 to 35 years of age, Female (53.2%) participants were more. We found that 38 (24.1%) persons were found to be in pre-diabetic stage, 57 (37.3%) are having high risk of getting diabetes. Conclusions: There is significant relationship between smoking, alcohol consumption and sedentary lifestyle (p<0.05) to the risk of diabetes as per Indian diabetes risk score.